2004
DOI: 10.1021/la040054c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface States on Finely Divided Supported Palladium Catalysts by Means of Inelastic Incoherent Neutron Scattering

Abstract: The purpose of the present investigation was to utilize the inelastic incoherent neutron scattering (INS) technique to reveal changes at the surface of technical catalysts under the influence of hydrogen in gas/solid interactions and during chemical reactions in a liquid-phase process. The formation and the properties of supported palladium hydride and changes of the hydrogen-related surface chemistry of the corresponding activated carbon supports in 20% Pd/C catalysts after short-term and long-term hydrogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
(96 reference statements)
0
30
0
2
Order By: Relevance
“…The INS study performed by Albers et al on Pd nanoparticles supported on AC showedt hat hydrogenation/dehydrogenation cycles could eliminate subsurface hydrides due to the restructuring of dislocations and lattice defects. [50] It was also shown that high temperature and pressure favored hydrogen spillover,l eading to the formation of surfacea morphous hydrogenated carbon. Analysis of as pent 5% Pd/C catalyst, which was used in the reaction of bromobenzene and styrene to form trans and cis-stilbene, revealed surface deposition of cis-stilbene, despite most of the product being trans-stilbene.…”
Section: Hydrogenous Speciesr Elevant For Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The INS study performed by Albers et al on Pd nanoparticles supported on AC showedt hat hydrogenation/dehydrogenation cycles could eliminate subsurface hydrides due to the restructuring of dislocations and lattice defects. [50] It was also shown that high temperature and pressure favored hydrogen spillover,l eading to the formation of surfacea morphous hydrogenated carbon. Analysis of as pent 5% Pd/C catalyst, which was used in the reaction of bromobenzene and styrene to form trans and cis-stilbene, revealed surface deposition of cis-stilbene, despite most of the product being trans-stilbene.…”
Section: Hydrogenous Speciesr Elevant For Catalysismentioning
confidence: 99%
“…The INS study performed by Albers et al. on Pd nanoparticles supported on AC showed that hydrogenation/dehydrogenation cycles could eliminate subsurface hydrides due to the restructuring of dislocations and lattice defects . It was also shown that high temperature and pressure favored hydrogen spillover, leading to the formation of surface amorphous hydrogenated carbon.…”
Section: Hydrogen Interactions With Supported Metal Catalystsmentioning
confidence: 99%
“…The detailed identification of the specific properties of the surface atomic layers of carboneous supports used for the preparation of Pd/C catalysts has been studied recently by means of inelastic incoherent neutron scattering. This technique allows the behavior of activated carbons and carbon blacks in the presence of adsorbed hydrogen to be studied and the vibrational states of protons on and inside carbon‐supported PdNPs and PtNPs to be identified 44a. Well‐known and typical applications of such materials are the hydrogenation reactions that are important for the synthesis of fine‐chemicals intermediates, vitamins, and pharmaceuticals 2.…”
Section: Solid Supports For Metal Nanoparticlesmentioning
confidence: 99%
“…Neuere Untersuchungen mit inelastischer inkohärenter Neutronenstreuung befassten sich insbesondere mit den spezifischen Eigenschaften der atomaren Oberflächenschichten von Kohlenstoffträgern für Pd/C‐Katalysatoren. Mit dieser Technik wurde das Verhalten von Aktivkohlematerial und Industrierußen (carbon blacks) in Gegenwart von Wasserstoffadsorbat sowie die Schwingungszustände von Protonen auf der Oberfläche und im Innern der auf dem Kohlenstoffträger fixierten Pd‐NPs und Pt‐NPs untersucht 44a. Häufige und charakteristische Anwendungen solcher Materialien sind Hydrierungsreaktionen zur Herstellung von Zwischenstufen in der Feinchemikaliensynthese sowie von Vitaminen und Pharmazeutika 2.…”
Section: Feste Träger Für Nanopartikelkatalysatorenunclassified